REMARKS ON THE *- TOPOLOGY - EL-MONSEF, M. E. ABD; LASHIEN, E. F.; NASEF, A. A. (Tamkang Journal of Mathematics, 1993)
An ideal I on a set X is a collection of subsets of X which is closed under the operations of subset (heredity) and finite union (additivity). Ideals are useful in generation new spaces from the old ones. The central theme in this paper is to give new characterizations and properties to the *-topology in the sense of Hashimoto or I-topology in the sense of Vaidyanathaswamy and τ^*(I) in the sense of Hamlett, Rose and Jankovic. Several connections between the *-topology and other corresponding ones are investigated.